Seasonal and spatial distribution of stoneflies in the Chubut River (Patagonia, Argentina) - Miserendino, Maria Laura (Hydrobiologia)
Longitudinal and seasonal distributions of Plecoptera species were examined along the Chubut River in the Patagonian Precordillera and Plateau, Argentina. Chubut River (>1000 km) is the largest river in the area and the hydrological regime is modified in the lower section by an artificial reservoir (Florentino Ameghino Dam). Quantitative samples were collected in 13 sites in the higher, middle and lower sections of the river basin. Sites were visited four times during 2004, and a total of 9 species and 5,772 individuals were collected in the study. Plecoptera richness decreased dramatically from the headwaters to the mouth of the river system. Two species, Antarctoperla michaelseni and Potamoperla myrmidon, were able to live below the impoundment but they were not abundant. Notoperlopsis femina and A. michaelseni abundances were higher in summer than in the other seasons, while L. jaffueli peaked in spring. Species-environmental relationships were examined using Canonical Correspondence Analysis and six independent variables were identified as the major factors structuring stoneflies assemblages. First axis was highly related to environmental variables reflecting the hydro-geological and land use gradients in the basin (conductivity, total suspended solids, periphyton Chlorophyll a). Second axis was more related to variables that changed seasonally (wet width, water temperature, soluble reactive phosphate). Fil: Miserendino, Maria Laura. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Patagonia Austral; Argentina